2017
DOI: 10.1542/peds.2017-0604
|View full text |Cite
|
Sign up to set email alerts
|

False-Positive Newborn Screening for Cystic Fibrosis and Health Care Use

Abstract: Higher use of outpatient services among FP infants may relate to a lengthy confirmatory testing process or follow-up carrier testing. However, increased rates of hospitalization might signal heightened perceptions of vulnerability among healthy infants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
1
20
0
1
Order By: Relevance
“…10 The number of allogeneic RBC units used in each facility was assumed to have a negative binomial error distribution-a common approach for modeling counts when overdispersion is likely. [11][12][13] Forward model selection based on the Akaike information criterion (AIC) 14 was used to determine the optimal metric, although the first step of model selection included only variables related to facility size (Table 1). Variables remained in the model only if they had a p value less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…10 The number of allogeneic RBC units used in each facility was assumed to have a negative binomial error distribution-a common approach for modeling counts when overdispersion is likely. [11][12][13] Forward model selection based on the Akaike information criterion (AIC) 14 was used to determine the optimal metric, although the first step of model selection included only variables related to facility size (Table 1). Variables remained in the model only if they had a p value less than 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…As designed, this screening algorithm does identify a large number of CF carriers, with 880 apparent carriers identified over the nine-year study period. The reporting of carrier status as part of a newborn screening program creates potential harms for families given a loss of autonomy for the newborn, concerns regarding the residual risk of disease, and heightened perception of the vulnerability of the infant [15]. Our program attempts to minimize these harms through further reducing the residual risk of disease with the second IRT sample, offering an optional sweat test for those with lingering concerns, and providing a dedicated CF liaison nurse to communicate with the families throughout the screening process.…”
Section: Program Performancementioning
confidence: 99%
“…The literature in this area has demonstrated mixed results . The largest study to date found that the false‐positive group had significantly higher rates of outpatient visits and inpatient hospitalizations for children three to fifteen months of age compared to matched controls whose screening results were negative . Such findings suggest connections between the lived family experience of uncertainty about the meaning of newborn screening results and subsequent medical decisions regarding the health of the infant.…”
Section: Essaymentioning
confidence: 99%